Частные военные компании. Терминология, правовой статус и классификация деятельности - Неелов, В.М. (Культура народов Причерноморья, 2014)
В статье рассматривается терминологический аппарат и политико-правовые аспекты
деятельности частных военных компаний. Автором делаются выводы о необходимости
совершенствования международно-правового законодательства в данной сфере, даётся классификация
по принципу выполняемых ими функций, приводятся основные примеры деятельности частных военных
компаний. У статті розглядається термінологічний апарат та політико-правові аспекти діяльності
приватних військових компаній. Автором робляться висновки щодо необхідності вдосконалення
міжнародно-правового законодавства в даній сфері, надається класифікація за принципом виконуваних
ними функцій, наводяться основні приклади діяльності приватних військових компаній. This article considers the terminology, political and legal aspects of the private military and security
companies’ activity. The use of non-state actors in wars is not a new phenomenon and has been taking place for
many centuries. The only new thing is a legal form, that’s been used in case of private military and security
companies. They can be classified by their activity: military provider companies; military consulting companies;
military support companies. Their legal status is not clearly defined but they have been extensively used not only
by states. The international organizations such as United Nations have been contracting with private military
and security companies for the different missions (mine clearance, security providing etc.). At the same time
there has been no clear international legislation and universal legal definition of private military and security
companies. The only one finished international document on this topic is the so called “Montreux Document”,
which hasn’t created any new norms about use of private military companies in combat zone and hasn’t defined
the status of the contractors. As a result this situation causes variety of problem in combat zone. There is a big
need of improvement of international law on private military and security companies.